Evaluation of Aspergillus flavus Growth on Weathered HDPE Plastics Contaminated with Diesel Fuel - Juan Valenzuela; César Sáez-Navarrete; Xavier Baraza; Fernando Martínez; Bastián Márquez (Microorganisms, 2025)
Plastic containers used for diesel storage represent an underexplored but significant environmental challenge due to hydrocarbon retention and prolonged weathering. This study evaluates the capacity of Aspergillus flavus to colonize and grow on high-density polyethylene (HDPE) surfaces contaminated with weathered and fresh diesel residues. Circular plastic samples from HDPE tanks exposed to environmental conditions for over two years (weathered) and for less than two months (non-weathered) were inoculated with A. flavus and incubated at 20 °C, 25 °C, and 30 °C. Growth kinetics were assessed through radial expansion and halo formation, quantified via digital imaging and ImageJ analysis. Results showed the most robust fungal growth occurred on weathered diesel-contaminated gray plastics at 30 °C, with colony areas exceeding 350 mm2 and halos over 3000 mm2. Conversely, white HDPE with fresh diesel showed limited and inconsistent growth, likely due to the presence of volatile hydrocarbons and polymer additives. These findings underscore the critical role of diesel aging and polymer characteristics in shaping fungal adaptability, providing a foundation for the development of environmentally sustainable bioremediation strategies targeting diesel-contaminated HDPE plastics.